2021
DOI: 10.3926/jiem.3592
|View full text |Cite
|
Sign up to set email alerts
|

Adaptations in SCOR based performance metrics of airline catering supply chain during COVID-19 pandemic

Abstract: Purpose: There is the propensity of the Airline catering supply chain to adapt their performance measures in order to meet desired service level due to the challenges of the Covid-19 pandemic. The aim of this paper is to develop a set of metrics for airline catering organization and explore the choices of SCOR based performance metrics during the Covid-19 pandemic.Design/methodology/approach: The SCOR framework is applied in the context of the airline catering supply chain to develop performance metrics. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…At the beginning of the article, a statement was made: the need to know the business processes has a strong influence on the individual calculation of the benefits and effort of implementing integrated IT systems. Therefore, conscious modelling of business processes plays an important role, especially in the first stages of an ERP class information system implementation (Rajaratnam, Sunmola, 2020). This state of affairs, provides answers to a set of questions:…”
Section: Process Approach As a Stage In The Implementation Of An Erp ...mentioning
confidence: 99%
“…At the beginning of the article, a statement was made: the need to know the business processes has a strong influence on the individual calculation of the benefits and effort of implementing integrated IT systems. Therefore, conscious modelling of business processes plays an important role, especially in the first stages of an ERP class information system implementation (Rajaratnam, Sunmola, 2020). This state of affairs, provides answers to a set of questions:…”
Section: Process Approach As a Stage In The Implementation Of An Erp ...mentioning
confidence: 99%
“…Furthermore, Bahraini et al (2013) declared that a large-scale flight catering production unit might employ over 800 staff to produce as many as 25,000 meals per day during peak periods. Rajaratnam and Sunmola (2021) declared that the meal served on board was more complex interactions has involved numerous parties in the supply chain, including governments, airlines, logistics service providers, caterers, meal suppliers, and customers. Fawzy et al (2016) reported that preparing meals for every passenger on every flight has been a challenging task, making it very important for the flight catering company to plan, control and design its supply chain.…”
Section: Inflight Catering Industrymentioning
confidence: 99%
“…The success of an airline catering company hinged on consistently providing high-quality service in ever-shrinking amounts of time. To improve their competitive position, airline catering organizations must focus on two key service goals: flexibility and perfection (Rajaratnam & Sunmola, 2021). On the other hand, the logistics role has been strengthened by the involvement of airline catering in the complex food supply chain for the demanding operations of airlines.…”
Section: Airline Catering Service Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…The Covid-19 outbreak has disrupted almost all economic sectors (Zhu, Chou & Tsai, 2020). Agriculture; oil, gas, and energy; tourism; retail; private healthcare; and many other industries are severely affected by the pandemic (Atayah, Dhiaf, Najaf & Frederico, 2021;Rajaratnam & Sunmola, 2021;Sopha, Arvianto & Tjahjono, 2022). The government of Malaysia imposed several restrictive measures to curb the spread of the pandemic such as travel restrictions, border closures, large-scale quarantines, bans on large-scale gatherings and dining in restaurants, and partial lockdowns (Budd & Ison, 2020).…”
Section: Introductionmentioning
confidence: 99%